(untitled) (14th CONSTRUCTAL LAW CONFERENCE | 10-11 October 2024, Bucharest, Romania, 2024)
Cold plates are heat transfer devices used in various industries such as aerospace, automotive, and telecommunications primarily to prevent overheating and ensure efficient operation of electronics and power electronics components. They are compact, flat heat exchangers designed mainly by dissipate heat to a liquid coolant. The present paper compares the thermal performance of three serpentine arrangements using a global resistance metric that accounts for thermal resistance and pumping power. Then, various Svelteness definitions that differ in the external length scale are investigated. All the designs hold the same five degrees of freedom: plate area, plate weight, pipe diameter, pipe bend radius ratio, and plate length ratio, but only the two latter ones are investigated here. Results show that the simple “S” shape performs better regarding the global resistance metric, mainly for configurations with low values of the ratio between the bend curvature radius and the pipe diameter (R/d). The three variants of Svelteness capture the general thermal performance very well, particularly the R/d effect and the impact of the plate aspect ratio (W/d). However, none of the Svelteness definitions considered could completely capture the performance differences among the different arrangements measured with the global resistance metric.